The First Polish Systematics of Spells against Illness. On the Forgotten Proposal of Józef Obrębski - Engelking, Anna (Poznańskie Studia Slawistyczne, 2012)
The author discusses the first Polish systematics of magic spells against illness, which was proposed by Józef Obrębski in a brochure Index for „Treating the Polish people” by Henryk Biegeleisen in 1931. Obrębski introduced a division of spells into 9 groups, separated on the basis  of their  content,  form and  function.  It  was  not  an  autonomous  development.  It  have been created for the needs of someone else’s work and on the margin of a broader classification of material in the field of folk medicine as a whole. However, the proposal of Obrębski  can  be  regarded  as  a  serious  outline covering  all  material  concerning  the  systematics  of spells against illness. In the following parts of the article the author sets the discussed work in  a  due  context,  locating  it  in  the  history  of Polish research  on  the  genre  of  spells.  She recalls the first nineteenth-century works and analyses a possible impact of the Obrębski’s systematics on the subsequent approaches to the subject.